O setor primário de santa maria na perspectiva do rural: a reestruturação das atividades produtivas - Ferro, Talita Luiza de Medeiros (2008)
The basic sector formed the economic base of RS represented, by the agriculture and the cattle raising. Because of the emphasis of the basic activities in the organization socio spacial of the gaucho State, Santa Maria basic sector also contributed for its economic development, next to other sectors (secondary and third). Meanwhile, this sector takes over emphasis in the municipal district, once that its production is applied, mainly, to demand of the place population. So that, the search had as principal apprehension to analyze the basic organization of Santa Maria through the basic sector, due its contribution in the agriculture and the cattle raising of the State and the economic development of the municipal district. According this thought liner the specific aims obtained: (a) analyze the process of formation and occupation of Santa Maria-RS and its influence in the actual spacial organization, checking the situation of cattle raising and agriculture; (b) Identify the different activities, introduced and developed in the basic sector of the municipal district and, its contribution in the place/regional development; (c) Check the changes and the result restructure of Santa Maria rural area, searching to identify the responsible factors for these changes. Methodological reflection divided the work in fazes. Firstly, accomplished a great bibliographic review about the topic in study. Later, the information collection in basic sources (area work) and in a second moment with IBGE dies (information). The area work realized through of the appliance of searching instrument, like this, elaborated an interview schedule to the Rural. Development Secretary of the Municipal District and EMATER. The final faze was formed whit the analysis and explanation of the information collections. What means in this search, we notice that Santa Maria Rural Area is concentrated in the district and the main basie activities are based in the agriculture, through the provisory agriculture of soybean and rice and in the cattle, raising, mainly the bovine cattle. However the dynamic of this productive sector occurred by the support of the original source and the inserction of the new activities stimulating the place economy. The new economic profiles are represented mainly by the Rural tourism and variety in the agricultural production, with vegetable and fruit, with precise localization in some district. The production is destinated, mainly to the place population, end the basic sector is the main furnisher of the products in the municipal district in study.